Economic Recovery Strategy: The Role of MSMEs Credit Access and Optimization of Regional Fiscal Stimulus in Islamic Economics Framework - Prajasari, Anniza Citra; Wijayanti, Dwi Marlina (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2024)
This paper aims to analyze the determinants of economic recovery in North Sumatra using district-based panel data from 2020-2022 using the Random Effect Model. Several variables derived from the implications of fiscal and monetary policies such as MSME credit access, inflation, the effectiveness of income spending, poverty, unemployment rate, and human development index were used to analyze economic recovery as proxied by GRDP per capita. Our findings indicated that the position of MSMEs' credit and relative poverty have a significant positive effect on economic recovery in North Sumatra. Conversely, the unemployment rate and human development index have a significant negative effect on economic recovery in North Sumatra. Inflation and the effectiveness of income spending have an insignificant effect on economic recovery in North Sumatra. These findings recommend that the government and the central bank should support increased access to MSME credit in terms of regulations, the availability of bank financial institutions, and allocations. In addition, it is crucial to maintain the effectiveness and increase indirect budget allocations for social fund posts that can be integrated with Islamic Social Funds such as Zakat, Infaq, and Shadaqah to address poverty and unemployment challenges to improve the community’s quality of life and accelerate economic recovery in North Sumatra.